General approach to N-heterocyclic carbenes with a fused tetracyclic core: ligands for suzuki-miyaura cross-coupling reaction - Sutar, Revannath L.; Kumar, Vinod; Shingare, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2014)
The synthesis of an N-heterocyclic carbene (NHC) based on a tetracyclic scaffold by using simple, general, and scalable chemistry is disclosed. The developed route is suitable for introducing multiple substitutions on the tetracyclic scaffold. The utility of the present NHC as a ligand in the Suzuki-Miyaura cross-coupling reaction is demonstrated with a low catalyst loading.
Keywords: C-C coupling; carbenes; Homogeneous catalysis; N ligands; synthetic methods

Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.